2008
DOI: 10.1007/s00277-008-0520-x
|View full text |Cite
|
Sign up to set email alerts
|

Effective screening for double heterozygosity of Hb E/α0-thalassemia

Abstract: One hundred and forty-one blood samples of hemoglobin E (Hb E) carriers were collected to define suitable cutoff values of Hb E level, mean corpuscular volume (MCV), and mean corpuscular hemoglobin (MCH) as screening indicators for detecting individuals with double heterozygosity for Hb E/alpha(o)-thalassemia. Based on the values that gave 100% sensitivity, Hb E < 26%, MCV < 74 fl, and MCH < 24 pg were selected. Further validation of these selected values in additional 152 heterozygous Hb E pregnant women reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
1
9
2
Order By: Relevance
“…At a Hb E cut-off value of 21.54% (mean þ SD), 95.0% of --SEA /β E trait show Hb E at lower than the cut-off value, while 94.0% of Hb E trait had Hb E levels higher than the cut-off value. These results were consistent with the previous study that showed Hb E level is the best indicator for screening of α-thal-1 in Hb E heterozygotes (15,16). However, coinheritance of the --SEA / deletion with β-thal trait or homozygous Hb E did not result in a marked reduction of Hb A 2 /E levels.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…At a Hb E cut-off value of 21.54% (mean þ SD), 95.0% of --SEA /β E trait show Hb E at lower than the cut-off value, while 94.0% of Hb E trait had Hb E levels higher than the cut-off value. These results were consistent with the previous study that showed Hb E level is the best indicator for screening of α-thal-1 in Hb E heterozygotes (15,16). However, coinheritance of the --SEA / deletion with β-thal trait or homozygous Hb E did not result in a marked reduction of Hb A 2 /E levels.…”
Section: Discussionsupporting
confidence: 95%
“…The limitation of our study is that the laboratory data for an iron study which is used for classification of microcytic anemia type was not available. Furthermore, mean corpuscular Hb (MCH) and red cell distribution width (RDW), which have been reported for limited information in classifying thalassemia and other microcytic anemias (16,19,20), were also not available. Consequently, we do not know whether MCH and RDW can be used as alternative screening tools for differentiation of the --SEA / deletion coinheritances from their counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Similar prevalence has been reported in Lao PDR and Cambodia. 8,9 This however cannot be applied to a homozygous Hb E as Hb analysis shows no Hb A for comparison. Among these are Hb E-related disorders.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the generation of useful cutoff level of 25% Hb E when analyzed using Hb-HPLC analyzer for effective screening of a double heterozygous for Hb E/α 0 -thalassemia. 8,9 This however cannot be applied to a homozygous Hb E as Hb analysis shows no Hb A for comparison. 10 In routine thalassemia screening, all cases of this Hb EE syndrome are therefore subjected to further analysis of α-thalassemia by DNA testing.…”
Section: Introductionmentioning
confidence: 99%